APLIKASI KAWASAN KONSERVASI BKSDA JAWA TENGAH SKW I BERBASIS WEB GIS (Information Technology and Telematics, 2013)
Research  is  underway  to  tointroduce  conservation  area  in  CentralJava, in  particular the  incoming  SKW  I,to  the  public.  So  that  people  care  abouthe importance of forests.Tropical forest in Central Java  isapproximately 1,148,400  squarekilometers,  consisting  of  protectedforest,  production  forest,  productionforest,  nature  reserve  areas  and  natureconservation  area. With  research  forestconservation  area  entrance  BKSDA SKW  I,  data  and  maps  to  the  publicinformed,  the  program  Arc  View,Dreamweaver, and Mapserver.The results of this study indicate,geographic  information systems  need  tobe  protected areas designed  to  introducethe  public  forests,  forests  that  remainstable.Keywords:  GIS,  Conservation  Areas,BKSDA Java, Web.